A driver in every car: when the auto industry says jump, do governments say "how high?". Issue 4 (17th July 2017) - Buigues, Pierre André
Abstract : Purpose: The purpose of this paper is to analyse the economic and political conditions that could explain why the governments in developed economies have intervened in the automobile industry. The author identifies the main reasons and the shortcomings of these public interventions. Design/methodology/approach: The paper presents different forms of public intervention in the automobile industry of various countries over the past few decades: infant industry, research and development (R&D), global climate change and global systemic crisis. Findings: The automobile sector is viewed by governments as a key sector and is subsidised for different reasons at different periods. The paper shows that governments give different reasons for public intervention in the automobile industry (infant industry, global climate change, R&D externalities, the global financial crisis, etc.). Whatever the theory, in practice, public interventions have a strong impact on the industry and its evolution. Practical implications: The paper highlights the importance for car manufacturers of monitoring the political initiatives of public authorities, which can affect the technological evolution of the automobile industry. Social implications: For households, the purchase of a car is quite important, and the political orientation of public subsidies in favour of one option over another, such as electric vehicles or an autonomous car, affects their choice. Originality/value: The paper examines an issue which has not previously been addressed by journals, yet which is crucial, i.e. the impact of government decisions on the evolution of an industry. The approach can also be applied to other sectors.